Epidemiological data, etiology, pathogenesis, risk factors, clinical manifestations, modern methods of diagnosis and treatment, prediction of the course of multiple myeloma (literature review) - Savuliak , H.R.; Novak, V.L. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Multiple myeloma (MM) is a neoplastic disease with a multistage course characterized by uncontrolled, multifocal proliferation of monoclonal plasma cells in the bone marrow, which produce monoclonal immunoglobulin or only its fragments, which lead to destruction of bone tissue and organ damage. Quite high rates of both morbidity and mortality from MM require more careful attention and deeper scientific research of this problem. Objective of the article is to investigate the epidemiology, etiology, pathogenesis, risk factors, clinical manifestations, modern methods of diagnosis and treatment, and also prediction of the course of MM. Methods. The following research methods were used: search, extraction and processing of information; assessment of the quality of sources; systematic literature review; content analysis. Research materials are thematic publications of ukrainian and foreign scientists. Results. MM accounts for ~1% of all malignant neoplasms and ~14% of hematological neoplasms worldwide. Etiological factors of MM: genetic predisposition, bacterial or viral infections, ionizing radiation, carcinogenic toxins. The clinical syndrome of MM is characterized by hypergammaglobulinemia, hypercalcemia, susceptibility to infections, and pathological fractures. Diagnosis of MM includes: general analysis of peripheral blood; diagnosis of serum and urine proteins; aspiration biopsy and trepanobiopsy of bone marrow; cytogenetic and molecular diagnostics; other laboratory diagnostics; radiography, CT, MRT and PET-CT. The main methods of treatment of MM: radiation therapy, chemotherapy, combined CT with the inclusion of new drugs, HDCT + autologous THSC. Prediction of the course of MM depends on the R-ISS stage, LDH level and high-risk cytogenetics. Conclusion. During the last years of modern oncohematology, we observe scientific achievements in the diagnosis and treatment of MM. A thorough study of the epidemiology, etiology and pathogenesis, risk factors and clinical manifestations of MM contribute to effective diagnosis and selection of the optimal treatment strategy and tactics, as well as determining the prognosis of the course of MM.